Giant Cell Tumor of Bone With Pseudosarcomatous Changes Leading to Premature Denosumab Therapy Interruption: A Case Report With Review of the Literature. (June 2016) - Sanchez-Pareja, Andrea; Larousserie, Frédérique; Boudabbous, Sana; Beaulieu, Jean-Yves; Mach, Nicolas; Saiji, Essia; Rougemont, Anne-Laure
Denosumab has shown promising results in the management of giant cell tumor of bone, a primary bone tumor with locally aggressive behaviour. We report a case of premature denosumab interruption due to radiological and clinical tumor expansion of a giant cell tumor of the distal ulna. Although denosumab is known to induce tumor regression, with progressive ossification and loss of the characteristic morphology of giant cell tumor of bone, the ulnar tumor specimen showed a moderately to highly cellular proliferation of short spindle-shaped cells, and no osteoclast-like giant cells. There were no abnormal mitotic figures. We considered the surgical specimen as a giant cell tumor of bone with partial regression after prematurely interrupted denosumab treatment. This case illustrates the diagnostic issues of an initially unfavourable evolution raising concern for malignancy, and the difficulties in histological assessment of a partially treated giant cell tumor of bone, that may mimic osteosarcoma.